Morphology of the male reproductive system and spermiogenesis in Hypanthidium foveolatum (Alfken, 1930) (Hymenoptera : Apidae : Megachilinae) - Silva, Ingrid Gracielle Martins da (2015)
The morphological aspects of male reproductive tract, spermiogenesis and spermatozoa are typical for each species and reflect its evolution, establishing a unique source of characters, which has been used to help solve phylogenetic problems. In Hypanthidium foveolatum the reproductive tract is composed of the testes comprising 28 testicular tubules, deferent ducts, seminal vesicles, accessory glands and an ejaculatory duct. The differentiation of spermatids occurs within cysts of up to 128 germ line cells each one. During the early spermatid phase, the nucleus resembles that of somatic cells. There follows a gradual chromatin condensation with an increase in nuclear electron density. In the spermatozoon, the nucleus contains heterogeneous chromatin with a loose appearance. The acrosome, shaped with the active participation of the Golgi complex, shows an electron-dense perforatorium involved by four electron-lucent acrosomal vesicle projections. The sperm tail presents an axoneme with a 9 + 9 + 2 microtubule pattern and two mitochondrial derivatives, which appear with different sizes. A dense crystalloid is formed initially in the mitochondrial matrix of the large derivative. The mitochondrial derivatives’ differentiation occurs concomitantly with an axoneme outgrowth. The centriolar adjunct is observed near the axoneme, anterior to the smaller mithocondrial derivative and exhibits an approximately triangular shape in cross-sections. Microtubules were observed around the head region and flagellar components during spermiogenesis.